2021
DOI: 10.1007/s11606-020-06385-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia Communication in Primary Care Visits for Patients with Diabetes

Abstract: BACKGROUND: Hypoglycemia is a common and serious adverse effect of diabetes treatment, especially for patients using insulin or insulin secretagogues. Guidelines recommend that these patients be assessed for interval hypoglycemic events at each clinical encounter and be provided anticipatory guidance for hypoglycemia prevention. OBJECTIVE: To determine the frequency and content of hypoglycemia communication in primary care visits. DESIGN: Qualitative study PARTICIPANTS: We examined 83 primary care visits from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated hypoglycemia is not frequently discussed during primary care visits, and discussions become even less frequent as patients become more medically complex. 22 There also remains a widespread perception among both patients and providers that a lower HbA 1c is better, even for older adults. 23 Indeed, this view was expressed by several patients in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated hypoglycemia is not frequently discussed during primary care visits, and discussions become even less frequent as patients become more medically complex. 22 There also remains a widespread perception among both patients and providers that a lower HbA 1c is better, even for older adults. 23 Indeed, this view was expressed by several patients in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia history should be assessed at every clinical encounter and should include hypoglycemic event frequency, severity, precipitants, symptoms (or lack thereof), and approach to treatment. It is essential to correlate home glucose readings, both from glucose meters and CGM systems, with symptoms and treatment, as individuals may experience and treat hypoglycemic symptoms without checking their glucose level (104), treat normal glucose values as hypoglycemic, or tolerate hypoglycemia without treatment either because of lack of symptoms or to avoid hyperglycemia.…”
Section: Hypoglycemia Risk Assessmentmentioning
confidence: 99%
“…Outpatient visits time limits: Primary care clinicians have limited time to address multiple health conditions with patients. 19,20 are often combined into a needs assessment. 26,27 Multiple HFE methods can be applied in each phase (Table 2).…”
Section: Clinical Time Limitations For Decision Support and Communica...mentioning
confidence: 99%